2023
DOI: 10.3389/fpls.2023.1189662
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of freezing tolerance in red clover (Trifolium pratense L.) germplasm of European origin

Abstract: Improvement of persistency is an important breeding goal in red clover (Trifolium pratense L.). In areas with cold winters, lack of persistency is often due to poor winter survival, of which low freezing tolerance (FT) is an important component. We conducted a genome wide association study (GWAS) to identify loci associated with freezing tolerance in a collection of 393 red clover accessions, mostly of European origin, and performed analyses of linkage disequilibrium and inbreeding. Accessions were genotyped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
(96 reference statements)
1
8
0
Order By: Relevance
“…4 Principal component analysis of traits recorded in 110 accessions from the EUCLEG red clover panel, grouped into four regions of origin. Canopy height in late October and clover rot resistance expressed during the following winter was recorded in the Norwegian EUCLEG field experiment [ 23 , 27 ], clover rot resistance data are from Frey et al [ 24 ] and freezing tolerance data from Zanotto et al [ 28 ]. Correlation coefficients between traits are given in Supplementary Table 8A …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Principal component analysis of traits recorded in 110 accessions from the EUCLEG red clover panel, grouped into four regions of origin. Canopy height in late October and clover rot resistance expressed during the following winter was recorded in the Norwegian EUCLEG field experiment [ 23 , 27 ], clover rot resistance data are from Frey et al [ 24 ] and freezing tolerance data from Zanotto et al [ 28 ]. Correlation coefficients between traits are given in Supplementary Table 8A …”
Section: Resultsmentioning
confidence: 99%
“…Larger sets of the EUCLEG red clover collection have been phenotyped in several field experiments [ 27 ] and in experiments under controlled conditions, including phenotyping of clover rot resistance of non-cold acclimated plants [ 24 ] and freezing tolerance of cold acclimated plants [ 28 ]. In the Norwegian field experiment, including 110 of the EUCLEG accessions [ 23 ], shoot growth in the establishment year was recorded with a plate meter at five points per plot in late September and in late October, in 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low LD in faba bean was previously reported ( Skovbjerg et al., 2023 ; Zhang et al., 2023 ) when comparing different faba bean diversity panels. Thus, the EUCLEG collection was the one showing lower LD blocks (higher recombination), an expected outcome in outbreeding species with high genetic diversity ( Pégard et al., 2023 ; Skovbjerg et al., 2023 ; Zanotto et al., 2023 ; Zhang et al., 2023 ). The rapid LD decay observed in this study (within roughly 150 kbp) revealed the variation present in a highly allogamous panmictic population and suggested that the MTAs identified (or the closely linked genes on either flanking side of the significant SNPs) were nearly or completely independent from each other and, hence, were sufficient for association mapping in faba bean.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with family-based QTL mapping, GWAS significantly increases mapping resolution and enables minor effect genes to be detected ( Abdurakhmonov et al., 2008 ). In recent years, GWAS studies have been reported in a range of legume crops such as soybean ( Hwang et al., 2014 ), pigeon pea ( Varshney et al., 2017 ), common bean ( Raggi et al., 2019 ), chickpea ( Varshney et al., 2019 ), red clover ( Zanotto et al., 2023 ), alfalfa ( Pégard et al., 2023 ), and the model legume Medicago truncatula ( Bonhomme et al., 2014 ). In faba bean, only a few GWAS studies have been reported so far which have identified candidate genes associated with frost tolerance ( Sallam et al., 2016 ); resistance to Ascochyta fabae ( Faridi et al., 2021 ); tolerance to herbicides ( Abou-Khater et al., 2022 ); drought, heat, and freezing tolerance ( Ali et al., 2016 ; Maalouf et al., 2022 ; Gutiérrez et al., 2023 ); agronomic traits ( Skovbjerg et al., 2023 ); and seed size ( Jayakodi et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%